IPhone application development for dummies - Goldstein, Neal (Wiley Pub., 2010)
"Make the most of the new 3.1 OS and Apple's Xcode 3.2! Learn to design small- or large-scale iPhone applications for profit or fun, create new iPhone apps using Xcode®, get your applications into the App Store and work with frameworks. Even if you're not a programming pro, you can turn your bright idea into an app you can market. The book also shows you how to get into the App Store!"--Publisher's description
Includes index. - "Making everything easier!"--Cover. - Print version record
Keywords: Developer's library; iPhone (Smartphone) -- Programming; Application software -- Development; Mobile computing; Computer software -- Development; iPhone (Téléphone intelligent); Programmation; Logiciels d'application; Développement; Informatique mobile; COMPUTERS; System Administration; Windows Administration; COMPUTERS; Operating Systems; DOS; COMPUTERS; Operating Systems; Windows Server & NT; COMPUTERS; Operating Systems; Macintosh; COMPUTERS; Operating Systems; Windows Workstation; iPhone (Smartphone); Programming; Application software; Development; Computer software; Development